In-Vitro Estimation of Total Phenolic, Flavonoid, Antioxidant Contents and Determination of Flavonoid, Amino Acid, and Vitamin Profiles of Ethanol Leaf Extract of Annona squamosa L. - Yakubu, Ojochenemi Ejeh; Audu, Jankada Patience; Adebisi, Arowora Kayode; Janya, Danjuma; Sunday, Abu Michael; Namuma, Shitta Nasisi; Ekpo, Fidelis Okii; Dauda, Maianguwa Abdulrashid; Sule, Josephine Maina; Umaru, Isaac John (African Journal of Clinical Medicine and Pharmacy Research, 2024)
Since the beginning of human civilisation, plants have been one of the main sources of medicines. The demand for pharmaceuticals, health products, food supplements, cosmetics, and medications made from plants is expanding. Since ancient times, traditional medicine has made use of the medicinal plant Annona squamosa. The aim of this research is to evaluate the total phenolic, flavonoid, antioxidant contents and the amino acid, and vitamin profiles of ethanol leaf extract of Annona squamosa L. By using the DPPH free radical scavenging experiment, the antioxidant potential of the ethanol leaf extracts was calculated, and the absorbance was determined at 517 nm. The IC50 value of the leaf was estimated to be 4.24 μg/mL. The Folin Ciocalteu method was used to measure the total phenolic content (TPC) spectrophotometrically. Total flavonoid content (TFC) was measured by aluminium chloride colorimetric assay and Quercetin was used as standard, the absorbance was measured at 520nm. The results showed that A. squamosa leaf is a rich source of phenolics and flavonoid (total Phenolic content: 26.01±1.45mg GAE/g and total flavonoid content: 71.20±35.74 mg QE/g). The high contents of phenolic compounds and flavonoid contents indicated that these compounds contribute to the antioxidant activity. A. squamosa can be regarded as promising plant species for natural plant sources of antioxidants with high potential value for drug preparation. The total amount of amino acids was found to be 331.887 uL Several detection and peak resolution were obtained from the HPLC analysis. The result showed the presence of eight amino acids including Asparagine (2.419uL), Threonine (50.828uL), Phenylalanine (37.533uL), Aspartic Acid (144.558uL), Leucine (8.650uL), Iso-Leucine (9.728uL), Glycine (54.060uL) and four vitamins Vitamin K (2.289mg), Vitamin B1 (958.597mg), Vitamin A (13.568mg) and Vitamin E (62.103mg).